Determination of the fracture closure pressure in fractural-cavity carbonate reservoirs using a failure criterion based on asperity behavior - Tian, Yuanyuan; Chen, Qing; Wu, Jvlin; Li, Kai; Yan, Changhui; He, Yi (Frontiers in Earth Science, 2024)
As fluid flow paths in fractural-cavity carbonate reservoirs, fractures have a significant impact on the production performance of carbonate reservoirs. In particular, well production depends on the apertures of the fractures, which vary with the effective stress acting on the fractures. Thus, predicting the fracture closure pressure is crucial for carbonate reservoir development. In our research, fracture closure pressures are derived using the Zienkiewicz–Pande failure criterion, which defines the pressure at which most asperities come into contact. The results reveal that fracture closure is influenced by the geo-stress field, rock mechanics, and spatial location of the fracture. Ultimately, the fracture closure pressure of typical wells located in different tectonic zones in the Shunbei Oilfield is calculated, and the results indicate that the fracture closure pressure in the Shunbei Oilfield is significantly affected by the dip of fractures and the angle between the fracture strike and maximum principal stress. To demonstrate the accuracy of the estimated fracture closure pressure, production performance corresponding to fracture closure was evaluated. It reveals that the flowing bottom pressure decreases rapidly and the recoverable oil reserves reduce when the pressure approaches the fracture closure pressure. This observation verifies that the fracture closure pressure determined using our formula is a feasible predictor of the production performance of fractural-cavity carbonate reservoirs.